Pseudoaneurysm of the Facial Artery Territory in an Odontogenic Infection Setting - Lopes Oliveira, MJ (2021)
A pseudoaneurysm of the facial artery is a rare event. It results from vessel wall disruption with blood tamponade from the surrounding tissues, and is usually caused by blunt facial trauma, with other etiologies rarely reported. We present two cases of a pseudoaneurysm in the facial artery territory in an odontogenic infection setting, highlighting the importance of computed tomography angiography for diagnosis and hastening treatment by vascular embolization.